The PEP++ study protocol: a cluster-randomised controlled trial on the effectiveness of an enhanced regimen of post-exposure prophylaxis for close contacts of persons affected by leprosy to prevent disease transmission - Duane C. Hinders; Anneke T. Taal; Suchitra Lisam; Aymée M. da Rocha; Nand Lal Banstola; Prativa Bhandari; Abhijit Saha; Jugal Kishore; Virginia O. Fernandes; Abu Sufian Chowdhury; Anna T. van ‘t Noordende; Liesbeth Mieras; et al. (BMC Infectious Diseases, 2024)
Abstract Background Leprosy is an infectious disease with a slow decline in global annual caseload in the past two decades. Active case finding and post-exposure prophylaxis (PEP) with a single dose of rifampicin (SDR) are recommended by the World Health Organization as measures for leprosy elimination. However, more potent PEP regimens are needed to increase the effect in groups highest at risk (i.e., household members and blood relatives, especially of multibacillary patients). The PEP++ trial will assess the effectiveness of an enhanced preventive regimen against leprosy in high-endemic districts in India, Brazil, Bangladesh, and Nepal compared with SDR-PEP. Methods The PEP++ study is a cluster-randomised controlled trial in selected districts of India, Brazil, Bangladesh, and Nepal. Sub-districts will be allocated randomly to the intervention and control arms. Leprosy patients detected from 2015 − 22 living in the districts will be approached to list their close contacts for enrolment in the study. All consenting participants will be screened for signs and symptoms of leprosy and tuberculosis (TB). In the intervention arm, eligible contacts receive the enhanced PEP++ regimen with three doses of rifampicin (150 − 600 mg) and clarithromycin (150 − 500 mg) administered at four-weekly intervals, whereas those in the control arm receive SDR-PEP. Follow-up screening for leprosy will be done for each individual two years after the final dose is administered. Cox’ proportion hazards analysis and Poisson regression will be used to compare the incidence rate ratios between the intervention and control areas as the primary study outcome. Discussion Past studies have shown that the level of SDR-PEP effectiveness is not uniform across contexts or in relation to leprosy patients. To address this, a number of recent trials are seeking to strengthen PEP regimens either through the use of new medications or by increasing the dosage of the existing ones. However, few studies focus on the impact of multiple doses of chemoprophylaxis using a combination of antibiotics. The PEP++ trial will investigate effectiveness of both an enhanced regimen and use geospatial analysis for PEP administration in the study communities. Trial registration NL7022 on the Dutch Trial Register on April 12, 2018. Protocol version 9.0 updated on 18 August 2022 https://www.onderzoekmetmensen.nl/en/trial/23060